1997
DOI: 10.1523/jneurosci.17-11-04441.1997
|View full text |Cite
|
Sign up to set email alerts
|

An Escalating Dose/Multiple High-Dose Binge Pattern of Amphetamine Administration Results in Differential Changes in the Extracellular Dopamine Response Profiles in Caudate-Putamen and Nucleus Accumbens

Abstract: Amphetamine (AMPH)-induced psychosis is most frequently associated with a chronic high-dose "binge" or "run" pattern of stimulant abuse, generally preceded by a period of gradually escalating doses of the drug. We showed previously that animals subjected to such a regimen of AMPH administration developed, over multiple daily binges, a unique pattern of behavioral response that included a decrease in stereotypy and a pronounced increase in locomotion. Because of the involvement of mesolimbic and mesostriatal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 39 publications
(41 reference statements)
3
15
0
Order By: Relevance
“…This observation is consistent with our previous finding of no decrease in brain levels of METH and AMPH as a function of ED pretreatment (Segal and Kuczenski, 1997c). Furthermore, although ED pretreatment does lead to a decrease in the caudate-putamen extracellular DA response and a corresponding attenuated stereotypy response to a subsequent binge (see below for further discussion), the decreased DA response is selective to caudate-putamen DA; that is, neither the nucleus accumbens DA response, nor the hippocampus NE response was attenuated (Segal and Kuczenski, 1997a;Kuczenski and Segal, 1997). Therefore, it appears that drug dispositional changes may occur only when METH pretreatment and/or binge doses are relatively high.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This observation is consistent with our previous finding of no decrease in brain levels of METH and AMPH as a function of ED pretreatment (Segal and Kuczenski, 1997c). Furthermore, although ED pretreatment does lead to a decrease in the caudate-putamen extracellular DA response and a corresponding attenuated stereotypy response to a subsequent binge (see below for further discussion), the decreased DA response is selective to caudate-putamen DA; that is, neither the nucleus accumbens DA response, nor the hippocampus NE response was attenuated (Segal and Kuczenski, 1997a;Kuczenski and Segal, 1997). Therefore, it appears that drug dispositional changes may occur only when METH pretreatment and/or binge doses are relatively high.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, to more closely approximate highdose METH abuse patterns, including the progressive increase in drug dose that typically precedes high-dose use, we have employed an ED-daily multiple administrations paradigm. Our previous results revealed that this stimulant protocol produced the progressive emergence of a unique behavioral profile and concomitant regionally specific DA response patterns in the striatum (Segal and Kuczenski, 1997a, b, c;Kuczenski and Segal, 1997). These effects appear to be both qualitatively as well as quantitatively different from the responses we have observed with any acute dose or single daily injection pattern of stimulant treatment.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Norepinephrine can also facilitate excitatory transmission by depressing the level of basal activity (Woodward et al, 1979). Thus, by virtue of their DA and NE amplifying capacity (Kuczenski and Segal, 1997;Solanto, 1998), stimulants may enhance task-specific signaling in target neurons within specific circuits.…”
Section: Pet Imaging Studies Of Adhd Adults and Effect Of Stimulant Dmentioning
confidence: 99%
“…The decreased AMPH-induced upregulation of Arc, NGFI-A, and NGFI-B expression might be considered to be a tolerance effect (Kuczenski and Segal, 1997;Shilling et al, 2000). While this is possible, rats challenged with 7.5mg/kg AMPH after twice daily injections of 7.5mg/kg AMPH do not exhibit locomotor behavioral tolerance (Persico et al, 1993).…”
Section: Discussionmentioning
confidence: 99%